Evaluation and molecular modelling of bis-Schiff base derivatives as potential leads for management of diabetes mellitus - Daoud Safa; Thiab Samar; Jazzazi Taghreed M. A.; Al-Shboul Tareq M. A.; Ullah Saeed (Acta Pharmaceutica)
Developing a medication to cure and manage diabetes mellitus complications is of interest in medicinal chemistry. Toward this end, six bis-biphenyl-salicylaldehyde Schiff base derivatives have been evaluated for their α-glucosidase inhibition, antiglycation and anti-inflammation potentials. Four compounds (compounds 2–5) showed an excellent α-glucosidase inhibitory effect superior to that produced by acarbose. Additionally, the docking study revealed that these compounds are anchored within the binding pocket of α-glucosidase via hydrogen bonding, π-stacking and hydrophobic interactions, comparable to a high number of hydrogen bonding involved in anchoring acarbose. Interestingly, all tested compounds showed varying degrees of antiglycation activity with superior activity for two of them (compound 1 and compound 6) compared to the standard rutin. Moreover, the results indicated an outstanding anti-inflammatory activity for two compounds (compounds 1 and 6) compared to ibuprofen.